Formation of a gender fair environment in educational institutions of Ukraine: European integration context - Kravets, V.; Kikinezhdi, O.; Vasylkevych, Y. (New Collegium, 2023)
The article is devoted to the topical problem of creating a gender fair environment in the national educational context of the human-centered paradigm, humanitarian security of Ukraine, and European integration processes. A theoretical and methodological analysis of the given problem is carried out adopting foreign and domestic approaches. Through the gender discourse, a conceptual model based on the principles of "partnership pedagogy" and the humanistic "matrix" of the philosophical and pedagogical heritage, the integration of competence-based, person-oriented and gender-based approaches in the context of the policy of academic integrity of higher education institutions is presented, and its effectiveness is experimentally proven. The content and structure and the leading factors and mechanisms of creating an educational environment for children and youth based on the principles of gender equality in the conditions of the New Ukrainian School are revealed. The author’s definition of the concept of "gender fair environment" as non-discriminatory, creative and developmental/creative, safe, health-preserving, inclusive, based on the principles of social justice, gender equality, child-centeredness, egalitarianism and gender parity is presented. The basic concepts of research are clarified, as well as the content, functions and features of a gender fair environment (GFE); its main components are singled out and characterized; on the basis of the defined criteria and indicators, the state of readiness of socionomic professions future specialists to the organization of the GFE is diagnosed. The principles of non-discriminatory education are substantiated, the psychological and pedagogical conditions for the formation of an egalitarian personality of a specialist are identified and empirically proven. Gender competence is considered in relation to intercultural competence as the main professional quality of a modern teacher. From the point of view of gender methodology, the principles, content and methods of psychological and pedagogical support of gender socialization of the individual are determined, and pedagogical monitoring is carried out to identify gender stereotypes and prejudices among students of higher education. The scientific and methodological support for the training of future teachers has been improved, the modernization of gender-educational technologies by means of IT in educational institutions of various levels has been carried out, and their effectiveness has been proven. The experience of the activity of the Scientific Research Center on Gender Education and Education of Pupil and Student Youth of the National Academy of Sciences of Ukraine – Ternopil Volodymyr Hnatiuk National Pedagogical University regarding the implementation of innovative gender-educational technologies in the educational and professional training of future specialists in socio-economic professions on the way to the EU and ensuring the national mechanism for building a parity democracy in Ukraine has been analyzed.